Religious and Intellectual Diversity in the Islamicate World and Beyond Volume II : Essays in Honor of Sarah Stroumsa - Michaelis, Omer,; Schmidtke, Sabine, (Islamic History and Civilization ;, 2024)
Religious and Intellectual Diversity in the Islamicate World and Beyond is a collection of essays in honor of Sarah Stroumsa, an eminent scholar who through the years has embodied and advanced the possibility of collaboration across borders. The volume is presented to her by scholars working on the study of the intellectual history of the Middle Ages, the intercultural contact and migration of knowledge in the Islamic world, and many other topics. Contributors: Binyamin Abrahamov, Camilla Adang, Anna Ayse Akasoy, Aleida Assmann, Jan Assmann, Meir M. Bar-Asher, José Bellver, Menachem Ben-Sasson, Haggai Ben-Shammai, Glen W. Bowersock, Rémi Brague, Godefroid de Callataÿ, Jonathan Decter, Michael Ebstein, Hussein Fancy, Carlos Fraenkel, Gil Gambash, Robert Gleave, Miriam Goldstein, Frank Griffel, Jaakko HämeenAnttila, Steven Harvey, Warren Zev Harvey, Meir Hatina, Geoffrey Khan, Gudrun Krämer, Ehud Krinis, Y. Tzvi Langermann, Daniel J. Lasker, Reimund Leicht, Gideon Libson, Menachem Lorberbaum, Maria Mavroudi, Jon McGinnis, Omer Michaelis, Yonatan Moss, David Nirenberg, Sari Nusseibeh, Olaf Pluta, Meira Polliack, James T. Robinson, Marina Rustow, Sabine Schmidtke, Gregor Schwarb, Ahmed El Shamsy, Mark Silk, Uriel Simonsohn, Daniel De Smet, Josef Stern, Guy G. Stroumsa, Sara Sviri, Alexander Treiger, Roy Vilozny, Ronny Vollandt, Elvira Wakelnig, Paul E. Walker, David J. Wasserstein, Tanja Werthmann, Dong Xiuyuan, Arye Zoref.